The effects of P2Y12 adenosine receptors’ inhibitors on central and peripheral chemoreflexes - Tubek, Stanislaw; Niewinski, Piotr; Langner-Hetmanczuk, Anna; Jura, Maksym; Kuliczkowski, Wiktor; Reczuch, Krzysztof; Ponikowski, Piotr (Frontiers in Physiology, 2023)
Ticagrelor’s most common side effect is dyspnea, which leads to premature withdrawal of this life-saving medication in 6.5% of patients. Increased chemoreceptors’ sensitivity was suggested as a possible pathophysiological explanation of this phenomenon; however, the link between oversenitization of peripheral and/or central chemosensory areas and ticagrelor intake has not been conclusively proved. We measured peripheral chemoreceptors sensitivity using hypoxic ventilatory response (HVR), central chemoreceptors sensitivity using hypercapnic hyperoxic ventilatory response (HCVR) and dyspnea severity before and 4±1 weeks after ticagrelor initiation in 11 subjects with chronic coronary syndrome undergoing percutaneous coronary intervention (PCI). The same tests were performed in 11 age- , sex- and BMI-matched patients treated with clopidogrel. The study is registered at ClinicalTrials.com at NCT05080478. Ticagrelor increased significantly both HVR (0.52±0.46vs0.84±0.69 Lmin-1%-1; p<0.01) and HCVR (1.05±0.64vs1.75±1.04 Lmin-1mmHg-1; p<0.01). The absolute change in HVR correlated with the change in HCVR. Clopidogrel administration did not influence significantly HVR (0.63±0.32vs0.58±0.33 Lmin-1%-1; p=0.53) and HCVR (1.22±0.67vs1.2±0.64 Lmin-1mmHg-1; p=0.79). Drug-related dyspnea was reported by three subjects in the ticagrelor group and none in the clopidogrel group. These patients were characterised by either high baseline HVR and HCVR or excessive increase in HVR following ticagrelor initiation. Ticagrelor in contrary to clopidogrel sensitizes both peripheral and central facets of chemodetection. Two potential mechanisms of ticagrelor-induced dyspnea have been identified: 1) high baseline HVR and HCVR or 2) excessive increase in HVR or HVR and HCVR. Whether other patterns of changes in chemosensitivities play role in the pathogenesis of this phenomenon needs to be further investigated.